Diethyl {(4-methoxyphenyl)[5-(4-nitrophenyl)-1,3,4-thiadiazol-2-ylamino]methyl}phosphonate - Yin, Li-He (International Union of Crystallography, 2008)
The title compound, C(20)H(23)N(4)O(6)PS, was synthesized by the reaction of N-(4-methoxybenzylidene)-5-(4-nitrophenyl)-1,3,4-thiadiazol-2-amine and diethyl phosphite. The thiadiazole and nitro-substituted phenyl rings in the molecule are approximately coplanar, the dihedral angle being 5.3 (2)°. The dihedral angle formed by the mean plane through all non-H atoms of both the thiadiazole and the nitro-substituted phenyl ring with the plane of the methoxy-substituted phenyl ring is 48.9 (2)°. In the crystal structure, molecules form centrosymmetric dimers as a result of N—H⋯O bonds involving amine H and phosphine oxide O atoms.